Evaluation of an Integrated Psychology Service in a Pediatric Emergency Department and Urgent Care. Issue 2 (12th February 2022) - Casher, Gabriel A.; Sutton, Brianne; Roosevelt, Genie; Simpson, Scott A.
Abstract : Objectives: Children visiting emergency departments (EDs) are disproportionately affected by mental health disorders. Integrated behavioral health models hold promise for improving care among ED patients. We implemented and evaluated a novel behavioral health service integrated psychology trainees in a safety net hospital's pediatric ED and urgent care. Methods: Consultations and interventions provided were identified from the service's patient registry. Patients treated by the service were matched based on age, sex, day, and month of presentation to control patients who received a brief assessment by a specialized psychiatric nurse or patients receiving comprehensive management in a psychiatric emergency service. Rates of ED return visits were obtained from local hospital records, and insurance claims were used to identify rates of psychiatric hospitalization and outpatient follow-up care. Results: The most commonly provided interventions among 71 intervention patients were assistance with connection to follow-up behavioral health treatment (65%), relaxation training (41%), and motivational interviewing (31%). These patients were matched with 142 comparison patients. There was no difference among groups in return rates within 90 days among intervention versus nurse assessment or psychiatric emergency service patients (25% vs 23% vs 13%, P = 0.14). Insurance claims data were available for 115 patients (54%): within 90 days, integrated care patients were less likely to have at least 1 outpatient claim (52% vs 78% vs 84%, P < 0.01), and there was no difference in rates of psychiatric hospital admission (18% vs 20% vs 24%, P = 0.83). Conclusions: Although this psychology-led integrated behavioral health service delivered a range of brief psychotherapeutic interventions, its impact on outpatient, inpatient, and emergency care was mixed. This lower follow-up rate among intervention patients may reflect the success of active psychological treatment in the ED, lower acuity among intervention patients, or implications of the study's safety net setting. The authors discuss this model's potential for enhancing mental health care in pediatric EDs.